2010
DOI: 10.1186/1746-1596-5-60
|View full text |Cite
|
Sign up to set email alerts
|

Use of anchorchip-time-of-flight spectrometry technology to screen tumor biomarker proteins in serum for small cell lung cancer

Abstract: BackgroundThe purpose of this study is to discover potential biomarkers in serum for the detection of small cell lung cancer (SCLC).Methods74 serum samples including 30 from SCLC patients and 44 from healthy controls were analyzed using ClinProt system combined with matrix-assisted laser desorption/ionization time-of-flight masss spectrometry (MALDI-TOF-MS). ClinProt software and genetic algorithm analysis selected a panel of serum markers that most efficiently predicted which patients had SCLC.ResultsThe diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…There are several studies published where MALDI/SELDI-based analyses of the low-molecular-weight fraction of serum/plasma proteome were applied for identification of peptide signatures specific for patients with head and neck cancer (30)(31)(32)(33)(34), colorectal cancer (19,(35)(36)(37)(38) and lung cancer (39)(40)(41)(42)(43)(44). All these works proposed differentiating peptides and multi-peptide signatures that discriminated between specimens collected from cancer patients and healthy donors, yet such cancer signatures were built of apparently different spectral components.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies published where MALDI/SELDI-based analyses of the low-molecular-weight fraction of serum/plasma proteome were applied for identification of peptide signatures specific for patients with head and neck cancer (30)(31)(32)(33)(34), colorectal cancer (19,(35)(36)(37)(38) and lung cancer (39)(40)(41)(42)(43)(44). All these works proposed differentiating peptides and multi-peptide signatures that discriminated between specimens collected from cancer patients and healthy donors, yet such cancer signatures were built of apparently different spectral components.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of honeybee venom employing both "bottom-up" and "topdown" strategies led to identification of only six known venom proteins and three unknown protein components, not identified earlier (Matysiak et al, 2011b;Peiren et al, 2005). Although, PAC targets are dedicated for the rapid screening analysis, many reports have shown that application of the classical AnchorChip MALDI plate facilitates better results (Du et al, 2010;Leung and Pitts, 2008;Zhang et al, 2008Zhang et al, , 2007. This plate, according to the manufacturer is preferred for high-throughput MALDI measurements that are performed in unattended, fully automatic mode.…”
Section: Honeybee Venom Analysis Applying Shotgun Proteomic Approachmentioning
confidence: 97%
“…Interestingly, low-molecular-weight peptides, such as S100A8 and fibrinogen, have been recognized to play important roles in physiologic and pathologic processes and could be used as relevant biomarker candidates (23,24). Recently, the mass spectrum that directly detects and differentiates short peptides has offered a promising approach for peptidomic biomarker discovery (8,12,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%